(untitled) (Laisvalaikio tyrimai, 2018)
This article analyzes the concept of information-communication management highlighting the trends of society and knowledge economy development, the necessary changes in the innovation, the importance of lifelong learning, information networks creation and partnership in exchange of knowledge Research background. To analyze the concept of information-communication management the following approaches should be used: 1) the economic approach that considers the attraction of new information, based on the concepts of utility and cost; 2) the analytical approach based on an analysis of the needs of information and communication; 3) the organizational approach that considers the information technologies in the context of their impact on the organizational aspects; 4) the systematic approach that considers the processing of the information based on a holistic, system-oriented, comprehensive information processing in the organization, which pays great attention to the optimization of communication channels, information, material means, working methods and costs. Research aim was to summarize the information-communication management problems analyzed in national and foreign authors’ studies, to identify the key characteristics and development trends. Methods. Information-communication management peculiarities are disclosed by doing the qualitative analysis of scientific literature content. The article aims to reveal the attitude of different authors, and the potential trends of information-communication management development. General scientific research methods – scientific literature logical analysis and synthesis were used for carrying out the theoretical study. Results. The main features of information-communication management are the following: 1) the conversion of information on the most important economic resource, which has global features and provides efficiency with the increasing the competitiveness and innovative development entities; 2) the growing influence of information on all the areas of human activity, turning it in terms of public consumption of the population; 3) the formation of an information intensive sector which occupies the dominant position in the new society; 4) the converting of the information sphere on the foundation and the basis of all economic activities. Intelligence, information and knowledge become more important resource in the XXI century (Osypenko, 2013). Conclusions. The main features of information-communication management are the following: the conversion of information on the most important economic resource, which has global features and provides efficiency with the increasing the competitiveness and innovative development entities; the growing influence of information on all the areas of human activity, turning it in terms of public consumption of the population; the formation of an information intensive sector which occupies the dominant position in the new society; the converting of the information sphere on the foundation and the basis of all economic activities. To solve these problems a fundamental theoretical basis of the concept of information-communication management has to be formed as well as the conditions for its implementation in the existing society have to be created. In modern scientific literature on information and communication management there is felt a lack of methodological reflection methods, techniques and methods of its implementation, institutional impact of the organizations on information processes and their implementation options in life. There is also a cognitive problem associated with deficiency of theoretical and practical reflection of the information and communication society and information-communication management. It contributes to the deepening of the basis for the analysis of cultural, economic and political factors of informatization. The solution of the specified problems require systemic solutions and development of the appropriate theoretical and conceptual approaches to this highly innovative discipline and new scientific field that affects many problems of the axiological, epistemological and ontological dimensions. Keywords: information-communication management, information society, informatization of society, information resources.